Dinamika Pengembangan Desa Wisata di Indonesia: Analisis Sistematik tentang Pendorong, Tantangan, dan Dampak - Mukti, Ari (Jurnal Pembangunan Nagari, 2025)
This study aims to analyze the dynamics of developing tourism villages in Indonesia through a systematic approach, focusing on driving factors, challenges, and resulting impacts. A Systematic Literature Review (SLR) approach was employed to synthesize relevant literature published between 2022 and 2024 using thematic content analysis methods. The findings reveal that key driving factors for tourism village development include the richness of local potential, multi-stakeholder collaboration, and support for infrastructure and innovation. However, significant challenges such as limited infrastructure, weak management, and insufficient digital promotion often hinder the sustainability of tourism villages. Additionally, the study highlights that the development of tourism villages generates substantial positive impacts, including local economic growth, community well-being, cultural preservation, and environmental conservation. Tourism villages serve not only as a tool for local economic development but also as a model for sustainable development that aligns social, economic, and environmental dimensions. To ensure the sustainability of tourism villages, this study recommends enhancing stakeholder synergy, improving infrastructure, optimizing digital promotion, empowering communities, mitigating risks, and implementing regulations for cultural and environmental preservation.